Analisis Kecurangan pada Pengelolaan Dana Desa dalam Perspektif Fraud Hexagon - Desviyana Desviyana; Yesi Mutia Basri; Nasrizal Nasrizal (Universitas Prasetiya Mulya, 2020)
This research aims to examine and analyze the factors that influence to fraud in the management of village funds in the perspective of hexagon theory in Rokan Hulu Regency ini Riau Province. The population in this study were all village officials in Rokan Hulu Regency using probability sampling method with Simple random sampling technique. This study use Partial Least Square (PLS) as method while Strcutural Equation Modeling (SEM) used as analytical tool. Based on the results of research using regression analysis only stimulus (obedience pressure), capability (competence), collusion (unethical act), oportunity ( Internal control) have a effect on fraud. Meanwhile, Razionalitation (organizational culture) and Ego (leadership style) do not affect fraud. This research was only carried out within the scope of the local government of Rokan Hulu district, so the results of this study were more representative of the situation locally. The results of this study confirm that there are several factors that can cause fraud to occur, and therefore village officials should jointly improve the quality of village fund management